The Evolution of Learning Transfer and Training Development in Achieving Sustainable Human Resource Management: A Bibliometric Review - Agustina, Isna Fitria; Irianto, Jusuf; Setijaningrum, Erna (RSF Conference Series: Business, Management and Social Sciences, 2024)
This research analyzes the evolution of learning transfer and training development in achieving sustainable human resource management (SHRM), an important part of achieving the 2030 SDGs target. The analysis was completed using a bibliometric review method of 161 articles in the Scopus database. The findings show that 454 authors from various developed and developing countries have contributed to this topic. Research on learning transfer and training development started in 1992 and continues to grow, but it was initially focused on achieving organizational performance. There is a shift in the purpose of learning transfer and training development which is now focused on achieving SHRM (HRM on financial, social, environmental, and organization) characterized by the keywords "natural resource management", "mental health", "healthcare", "female", which shows the importance of learning transfer and training development in achieving SDGs 3 (mental and well-being) and SDGs 4 (gender equality), as well as maintaining a balance of production and consumption through managing natural resources relevant to SDGs 12 and 13. Learning and training in the environmental aspect are interesting to research, indicated by the highest citation achievement in green human resource and green training articles with 184 citations. Learning transfer and training development also focus on technology training, such as cybersecurity and blockchain training. Furthermore, general topics such as learning and training to improve innovation, job satisfaction and organizational culture are still discussed.